2014
DOI: 10.1159/000357306
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Repair Activities of Undifferentiated and Classically and Alternatively Activated Macrophages

Abstract: Objective: Macrophages play a critical role in wound repair. However, the specific role of the different macrophage subtypes in wound repair remains incompletely understood. The aim of this study was to compare the wound repair activities of undifferentiated macrophages (M0), classically activated macrophages (M1) and alternatively activated (M2) macrophages. Methods: The macrophage repair activities of intestinal wounds were evaluated using in vitro and in vivo models. Results: All three macrophage subtypes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
(34 reference statements)
2
25
0
Order By: Relevance
“…Although several subtypes of M2-like macrophages have been described and not all of them perfectly fit into that paradigm,16 an essential role of M2-like macrophages for the maintenance of mucosal homeostasis and tissue remodelling is undisputed 14. Particularly, M2-like macrophages have also been implicated in the process of intestinal wound healing 41. While the initial inflammatory phase after tissue injury is dominated by inflammatory macrophages, which fight potential infectious stimuli by secretion of proinflammatory cytokines, tissue degradation and recruitment of other immune cells, the proliferative phase of wound healing is orchestrated by alternatively activated wound healing macrophages that prevent further tissue damage, secrete growth factors and promote neoangiogenesis 17 26.…”
Section: Discussionmentioning
confidence: 99%
“…Although several subtypes of M2-like macrophages have been described and not all of them perfectly fit into that paradigm,16 an essential role of M2-like macrophages for the maintenance of mucosal homeostasis and tissue remodelling is undisputed 14. Particularly, M2-like macrophages have also been implicated in the process of intestinal wound healing 41. While the initial inflammatory phase after tissue injury is dominated by inflammatory macrophages, which fight potential infectious stimuli by secretion of proinflammatory cytokines, tissue degradation and recruitment of other immune cells, the proliferative phase of wound healing is orchestrated by alternatively activated wound healing macrophages that prevent further tissue damage, secrete growth factors and promote neoangiogenesis 17 26.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors showed M2(IL-4ϩIL-13) macrophage adoptive transfer had a consistent effect when administered 6 h after DNBS treatment in three consecutive rounds, each round spaced 2 wk apart. Enderlin Vaz da Silva and colleagues (22) showed that intravenous administration of bone-marrow derived M0(unpolarized) or M2(IL-4) but not M1(IFN-␥) macrophages on the 3rd and 4th day after beginning DSS administration increased ulcer repair, despite the fact that all three types of macrophages reached the inflamed colon in comparable amounts. Lastly, it has recently been shown that Akt-2 deficiency protects mice from DSS colitis, and that Akt-2-deficient macrophages develop an M2 phenotype in vitro (3a).…”
Section: Cd169mentioning
confidence: 99%
“…Wound macrophages have hybrid M1/M2 activation phenotypes that enable their plasticity and ability to switch between functions during the healing process . In intestinal wounds of mice, both undifferentiated macrophages and M2 macrophages contributed to tissue repair, supporting the new view that M2 phenotypes may not be the sole macrophage population responsible for tissue repair . New subset macrophage classifications have been utilized based on the versatile role of macrophages in the healing process and include: 1 classically activated macrophage (M1) observed after stimulation with LPS or IFN‐γ, and 3 M2 subsets (M2a, M2b, and M2c), also known as wound‐healing macrophages, which produce high levels of IL‐10 and low levels of IL‐12.…”
Section: The Role Of Macrophages In Wound Healingmentioning
confidence: 99%